2022
DOI: 10.3390/coatings12060759
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties and Residual Stress Measurement of TiN/Ti Duplex Coating Using HiPIMS TiN on Cold Spray Ti

Abstract: This study investigated the mechanical properties and the residual stress of high-power impulse magnetron sputtering (HiPIMS) titanium nitride (TiN) thin film capping on cold spray titanium (Ti) coating. This TiN/Ti duplex coating was deposited on the Ti substrate, and the cold spray titanium (Ti) coating was prepared in three cases with different numbers of layers. The study determined Young’s modulus, hardness, and roughness of TiN thin film and cold spray Ti coatings by nano-indentation and AFM. The residua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…These hard coatings act as protective barriers, enhancing resistance to abrasion, corrosion, and high temperatures. This approach, known as duplex surface engineering, leverages multiple established surface technologies to create a multi-layered coating, ensuring the longevity and reliability of critical components operating in demanding environments [12][13][14][15][16]. Goldbaum et al [17] developed a duplex structure using cold spray technology and PVD for aerospace part repair.…”
Section: Introductionmentioning
confidence: 99%
“…These hard coatings act as protective barriers, enhancing resistance to abrasion, corrosion, and high temperatures. This approach, known as duplex surface engineering, leverages multiple established surface technologies to create a multi-layered coating, ensuring the longevity and reliability of critical components operating in demanding environments [12][13][14][15][16]. Goldbaum et al [17] developed a duplex structure using cold spray technology and PVD for aerospace part repair.…”
Section: Introductionmentioning
confidence: 99%
“…In turn, the use of high-power pulsed magnetron sputtering makes it possible to use Ti duplex coatings in the aerospace industry. 5,6 Studies indicate that surface pre-treatment and coating methods are crucial to achieve the best characteristics of coatings. For instance, it has been shown that a pre-treatment of a substrate surface has a positive effect on the morphology and properties of electrophoretically deposited biopolymer coatings.…”
Section: Introductionmentioning
confidence: 99%
“…In turn, the use of high-power pulsed magnetron sputtering makes it possible to use Ti duplex coatings in the aerospace industry. 5,6…”
Section: Introductionmentioning
confidence: 99%
“…However, due to the large internal stresses and poor toughness of thin PVD coatings caused by ion bombardment with high energy during deposition, the coatings suffer from the comprehensive properties of high hardness and weak adhesion to soft metallic substrates (refers to iron, steel and other lowhardness metal materials, especially light alloys, such as Mg, Al, and Ti). In particular, the substrate easily undergoes the serious plastic deformation under the heavy load conditions, which can thereafter lead to catastrophic delamination/flaking of the top PVD protective coating [48][49][50]. Many researchers have recently proposed a new "duplex coating" system based on HVOF and PVD [45,[50][51][52][53][54][55][56][57][58][59][60].…”
Section: Introductionmentioning
confidence: 99%